2017
DOI: 10.1111/bcpt.12790
|View full text |Cite
|
Sign up to set email alerts
|

Human BJ Fibroblasts is an Alternative to Mouse BALB/c 3T3 Cells in In Vitro Neutral Red Uptake Assay

Abstract: The OECD GD 129 BALB/c 3T3 neutral red uptake (NRU) assay is a standardized test method for estimating starting dose for an acute oral systemic toxicity test in rodents. Mouse BALB/c 3T3 fibroblasts are the most commonly used cells in the NRU assay. We have previously transferred and validated BALB/c 3T3 NRU assay in our GLP laboratory. Subsequently, in order to obtain more human-relevant cytotoxicity data, we performed an intralaboratory validation using human BJ fibroblasts in the NRU assay instead of mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
16
0
3
Order By: Relevance
“…It is important to note that the responses of HepG2, Caco‐2, A549 and HMEC‐1 to each chemical did not differ significantly from each other (Figure ). Our findings are in line with those of a previous report, which found that half the tested chemicals (13 out of 26) were more toxic to mouse BALB/c 3T3 cells than to human BJ fibroblasts; the remaining tested chemicals were equally (7 out of 26) or less toxic (6 out of 26) to 3T3 than BJ fibroblasts . These results are also in accordance with observations in MTT assay indicating that the 3T3 cell line was more sensitive than BJ human fibroblasts to various nanoparticles: the IC 50 values obtained for each type of nanoparticles were roughly 1.5‐fold lower in the experiments with the 3T3 mouse fibroblasts than with the BJ human fibroblasts .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is important to note that the responses of HepG2, Caco‐2, A549 and HMEC‐1 to each chemical did not differ significantly from each other (Figure ). Our findings are in line with those of a previous report, which found that half the tested chemicals (13 out of 26) were more toxic to mouse BALB/c 3T3 cells than to human BJ fibroblasts; the remaining tested chemicals were equally (7 out of 26) or less toxic (6 out of 26) to 3T3 than BJ fibroblasts . These results are also in accordance with observations in MTT assay indicating that the 3T3 cell line was more sensitive than BJ human fibroblasts to various nanoparticles: the IC 50 values obtained for each type of nanoparticles were roughly 1.5‐fold lower in the experiments with the 3T3 mouse fibroblasts than with the BJ human fibroblasts .…”
Section: Discussionsupporting
confidence: 92%
“…For example, Knels et al recently reported the beneficial effects of infrared A on 3T3 fibroblast culture, which was regarded as a well‐defined cell line with a standard, stable growth rate . An additional argument given in favour of using the 3T3 cell line is that it is a globally accepted cell line for use in the neutral red uptake assay (NRU), which is a standardized method for acute toxicity testing in rodents . Another reason for using the 3T3 fibroblasts by some researchers is their good responsiveness to external stimuli; however, this feature has been primarily ascribed to cardiac fibroblasts: the main cellular constituents of the heart .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions of each well were then transferred to 96-well plate and read at 450 nm by microplate reader [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further data of in vitro experiments are needed for the weight of evidence approach in risk assessment and licensing . New end‐point tests predicting the mechanism by which a genotoxic chemical is acting to damage DNA were presented and the importance of cytotoxicity discussed . Techniques measuring alterations in yH2AX and p53 activation can be used to characterize the mode of action at various concentrations .…”
mentioning
confidence: 99%